CORRECTIVE LOGARITHMIC WORK STEPS WITH CHILDREN WITH IMPAIRED PRONUNCIATION OF SOUNDS - Tajimuratov Azizbek Jaksymuratovich; Reymbaeva Dilnaz Bakhtiyarovna (Journals Park Publishing, 2023)
In this article, the task of logopedic rhythms and correction of speech defects. Information on the elimination of speech and movement defects using logarithmic means is given.
Keywords: Logopedic rhythms, didactic materials, didactic houses, articulatory apparatus, Phonetic-phonemic speech deficiency.